Interleukin-31 Signaling Bridges the Gap Between Immune Cells, the Nervous System and Epithelial Tissues - Nemmer, Jana Maria; Kuchner, Marcus; Datsi, Angeliki; Oláh, Péter; Julia, Valérie; Raap, Ulrike; Homey, Bernhard (Frontiers in Medicine, 2021)
Pruritus represents one of the most common symptoms in dermatology and general medicine. Chronic pruritus severely impairs the quality of life of affected patients. During the last two decades a number of modulators and mediator of pruritus have been identified. Recently, Interleukin (IL)-31 and its receptor complex attracted significant interest, as clinical phase two studies demonstrated therapeutic efficacy of the neutralizing IL-31 receptor A (IL-31RA) antibody nemolizumab in patients suffering from atopic dermatitis or prurigo nodularis. IL-31 has also been shown to play relevant roles in allergic contact dermatitis, urticaria, mastocytosis, allergic rhinitis and asthma. Here, we summarize the current knowledge of the novel cytokine IL-31 and its receptor regarding cellular origin, regulation, signaling pathways and their involvement in biological processes such as pruritus, neuronal growth, inflammation, barrier dysfunction and tissue remodeling.